Petrogenesis of the early Permian Hongliujing granite complex in the Chinese Eastern Tianshan orogen: Evidence for crustal growth in the Central Tianshan microcontinent - He, Zhen Yu; Klemd, Reiner; Lu, Tian Yu; Yan, Li Li; Xiang, Hua (Geological Society of America Bulletin, 2024)
The generation and modification of silicic magma systems are essential processes in resolving the differentiation of continental crust. This understanding motivated the geochronological and geochemical study of the early Permian Hongliujing granite complex, consisting of quartz monzonite, granite, and leucogranite in the Central Tianshan microcontinent of the southern Central Asian Orogenic Belt. Laser ablation–inductively coupled plasma–mass spectrometry (LA-ICP-MS) zircon U-Pb dating of the Hongliujing complex rock units revealed almost identical ages (279 ± 2 Ma to 270 ± 2 Ma). The high-silica leucogranite and granite are characterized by positive Rb and negative Eu anomalies and Ba, Sr, P, and Ti depletions. The zircon trace elements are characterized by relatively low Ti and Th/U and high Yb/Gd. In contrast, the quartz monzonite and its mafic microgranular enclaves display minor negative Ba, Sr, P, Ti, and Eu anomalies, while the zircon trace elements are characterized by relatively high Ti and Th/U and low Yb/Gd. The complex has similar zircon Hf and whole-rock Nd isotopic compositions, with Hf and Nd model ages younger than 1.4 Ga, suggesting that their magmas were derived from an isotopically depleted mantle, with some contributions from crustal melts. The leucogranites further showed relatively large variations of εHf(t) and lower εNd(t) values, implying that their magma was affected by higher amounts of crustal contamination. We suggest that crystal-melt segregation was the major mechanism responsible for the evolution of the magmatic system, and that the early Permian magmatism represents a crust-forming episode triggered by slab rollback of the subducting South Tianshan oceanic plate beneath the eastern Central Tianshan microcontinent. Thus, our study reveals that microcontinents with Precambrian crustal basement were major sites of juvenile continental growth during the accretionary evolution of the Central Asian Orogenic Belt.
CRIS-Team Scopus Importer:2024-08-16